Analysis of Risk Factors for Acute Heart Failure in Patients with Dilated Cardiomyopathy and Persistent Severe Functional Mitral Regurgitation Despite Cardiac Resynchronization Therapy - Buriak, R. V.; Rudenko, K. V.; Krykunov, O. A. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Congestive heart failure resulting from non-ischemic dilated cardiomyopathy (DCM) with secondary functional mitral regurgitation (FMR) is associated with poor prognosis. Medical treatment results in a 1-year survival of 52% to 87% and a 5-year survival of 22% to 54%, with highest survivals observed in more recent years, probably reflecting improvements in medical therapy. Non-surgical interventions involve cardiac resynchronization therapy. In addition to medical treatment, cardiac resynchronization therapy (CRT) should be considered in patients with New York Heart Association (NYHA) class II– IV HF, left ventricular ejection fraction (LVEF) =35%, normal sinus rhythm and left bundle branch block with QRS >150 ms. In these patients, CRT can also facilitate left ventricular (LV) reverse remodeling and reduce associated FMR. The aim of this study was to investigate the features of symptomatology and to analyze the risk factors for acute heart failure (AHF) in patients with DCM and persistent severe functional mitral regurgitation despite CRT and optimal guideline-directed medical therapy (GDMT). Materials and methods. After providing informed consent, 144 patients with severe FMR were involved in the study. Concomitant tricuspid valve regurgitation was registered in 142 (98.6%) cases. The median LVEF was 27.0 (23.0-31.6)%. 40 (27.8%) patients had a permanent form of atrial fibrillation, and 24 (16.7%) patients had a first-degree atrioventricular node block. The median NT-proBNP was 2600 (2133-3200) pg/ml, indicating the presence of severe chronic heart failure. Results. The median term after CRT device implantation was 36 (3.5-60) months. A comparative analysis between DCM patients with and without CRT revealed statistically significant differences between clinical characteristics, namely: age (p=0.020), lower heart rate (p=0.004), lower hemoglobin (p=0.017), higher erythrocyte sedimentation rate (ESR) (p=0.000) and more frequent AHF at the hospital stage (p=0.030). The incidence of AHF at the hospital stage was 13.8% in patients with CRT and 3.5% in those without CRT. The calculated odds ratio of AHF was 4.44 (95% confidence interval (CI) 1.039-18.971), and the relative risk of AHF was 3.966 (95% CI 1.054-14.915). Discussion. FMR has been reported to persist in about 20% to 25% of CRT patients and, in an additional 10% to 15%, it may actually worsen after CRT. In this subset of CRT non-responders, reduced reverse remodeling, increased morbidity, and increased mortality have been reported compared with CRT patients in whom FMR was significantly reduced or abolished. Conclusions. The results of our study demonstrate that severe functional mitral regurgitation despite cardiac resynchronization therapy in patients with dilated cardiomyopathy is a significant risk factor for AHF and subsequent hospitalizations for heart failure.